Characterising the activity, lifestyle behaviours and health outcomes of UK university students: an observational cohort study with a focus on gender and ethnicity - Matthew J. Savage; Eleanor L. Procter; Daniele Magistro; Philip J. Hennis; James Donaldson; Anika Leslie-Walker; Bethany A. Jones; Ruth M. James (BMC Public Health)
Abstract Background Health-related outcomes and behaviours in university students are known to be poor relative to the general population. The substantial contextual shifts related to the COVID-19 pandemic, combined with increased numbers of students from minoritised ethnicity backgrounds and presenting as trans and gender diverse (TGD), means that up-to-date information is unavailable. The primary aim of this study was therefore to characterise the current movement, dietary and lifestyle behaviours, mental health, and Body Mass Index (BMI) of UK university students and assess differences between genders and ethnic groups. Methods An online, self-report survey was administered across three years (2021–2023). Three independent cohorts of university students’ (n = 6,327) completed the survey on four key topic areas. One-way ANOVAs were used to assess differences between genders (men, women, TGD), and independent samples t-tests were used to assess differences between ethnic groups (White, Minoritised Ethnicity). Results 30% of students were not meeting physical activity guidelines, 54% were sedentary for ≥ 6 h·d− 1, 83% had poor diet quality, 51% were in high or increased risk groups for alcohol consumption, 18% experienced terrible or poor sleep quality, and 32% were overweight or obese. Gender differences were present for all variables other than walking physical activity (WPA) (P < 0.05), with men having better mental health and engaging in healthier movement and sleeping behaviours, whereas women had more healthful dietary and drinking behaviours, and TGD students had poorer outcomes compared to cis-gender students in most domains. Differences between White and minoritised ethnicity students were present for all variables other than sedentary behaviour, diet quality, WPA and BMI (P < 0.05); students of minoritised ethnicity engaged in better movement, drinking and sleep behaviours in addition to having more positive mental health than White students. Conclusion The findings of the current study provide an update on the landscape of UK university students’ health and health-related behaviours. Overall, health-related outcomes and behaviours are poor in this population and these data suggest that gender and ethnicity play a role in determining students’ health and health-related behaviours. Therefore, these factors should be considered when developing strategies to promote healthy living in the context of higher education.